Über den lokalen Greuzwertsatz für Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила. О локальной предельной теореме для плотностей P. Survila. Apie ribinę lokalinę teoremą tankiams